2007
DOI: 10.1590/s0103-50532007000500018
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation and antimicrobial activity of Myrcia myrtifolia essential oils

Abstract: Os óleos essenciais das folhas, flores e frutos de Myrcia myrtifolia DC foram coletados ao longo dos anos de 2002 e 2003 e foram analisados utilizando CG-DIC e CG-EM. No total foram identificados 28 componentes sendo que o α-pineno foi a substância predominante em todas as amostras analisadas apresentando-se em concentrações que variaram entre 61.5 e 90.9%. As propriedades antimicrobianas do óleo essencial das folhas coletadas em outubro de 2002 foram avaliadas contra seis bactérias, duas leveduras e cinco fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 10 publications
1
22
0
1
Order By: Relevance
“…(2E,6E)-Methyl farnesoate (14.39%) and hexadecanoic acid (22.05%) were the main compounds found in the stem bark, while in the flowers, the main compounds were espathulenol (7.36%), (2Z,6Z)-farnesol (10.65%) and (2E,6E)-methyl farnesoate (14.28%). Sesquiterpenes were predominant in the flowers, as has previously been found in Myrcia fallax; however, guaiol (27.5%) and aristolone (24.5%) were the primary compounds found in Myrica fallax, while monoterpenes, represented by α-pinene were the main components (62-87.3%) present in Myrcia myrtifolia DC (Cerqueira et al, 2007;Alarcón et al, 2009).…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…(2E,6E)-Methyl farnesoate (14.39%) and hexadecanoic acid (22.05%) were the main compounds found in the stem bark, while in the flowers, the main compounds were espathulenol (7.36%), (2Z,6Z)-farnesol (10.65%) and (2E,6E)-methyl farnesoate (14.28%). Sesquiterpenes were predominant in the flowers, as has previously been found in Myrcia fallax; however, guaiol (27.5%) and aristolone (24.5%) were the primary compounds found in Myrica fallax, while monoterpenes, represented by α-pinene were the main components (62-87.3%) present in Myrcia myrtifolia DC (Cerqueira et al, 2007;Alarcón et al, 2009).…”
Section: Resultssupporting
confidence: 51%
“…The work of Cerqueira et al (2007) on seasonal variation and antimicrobial activity and Alarcón et al (2009) on chemical composition and antibacterial activity are examples of such antimicrobial studies for the genus Myrcia. Souza (2009) analyzed the chemical composition of nine species of the Myrtaceae family, two of which belonged to the genus Myrcia, Limberger et al (2004) analyzed the composition of nine species of the genus Myrcia, and Zoghbi et al (2003) analyzed three species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Samaranayake et al (1995) demonstrated that C. krusei is more hydrophobic than other species. This physicochemical characteristic could at least partly explain the susceptibility of this yeast to the oils due to the hydrophobic nature of the majority of the components of the essential oil (de Cerqueira et al, 2007).…”
Section: Resultsmentioning
confidence: 97%
“…This difference in antifungal activity between essential oils from plants of the same species can be explained by the chemotype (chemical composition), geographical region of plant collection, age of plant, extraction method of oils, method used to assess the antifungal activity or by the intra or inter species differences (Samaranayake et al, 1995;Cruz et al, 2007;Maksimovic et al, 2008). Sharma & Tripathi (2008) have shown that the antifungal activity of essential oils is better evaluated in liquid than in solid media, since in the latter, the hydrophobic nature of the majority of essential oil components hamper uniform diffusion of these substances through the agar medium (de Cerqueira et al, 2007). We used the standard microdilution methods M38-A and AFST-EUCAST for the evaluation of antifungal susceptibility of filamentous fungi and yeasts, respectively.…”
Section: Resultsmentioning
confidence: 99%